BIM associated with Facility Management: A Case study of the semi-intensive unit at the Recife-PE Area Military Hospital - Oliveira, Alita Andrade Gama de; Valério, Bianca Maria Vasconcelos; Soares , Willames de Albuquerque (National Journal of City Management, 2026)
Objective – To develop a model for the application of Building Information Modeling (BIM) associated with Facilities Management (FM) in a hospital Semi-Intensive Unit, based on the diagnosis of the existing management processes in the operational Semi-Intensive Unit of the Military Area Hospital in Recife. Methodology – The analysis was conducted through data collection from the hospital, on site visits to the study location, qualitative data analysis, diagnosis of existing management processes, modeling of the study environment, and simulations using specific software. Originality/Relevance – Application of BIM associated with Facility Management (FM) in the use, operation, and maintenance phase within the hospital context is highly relevant. The aim is to achieve more efficient management, considering that healthcare facilities involve complex systems of installations, equipment, and spaces that require continuos monitoring. Results – It was observed that the integration between BIM and FM in hospital environments represents a concrete opportunity to advance the management of physical and operational assets in healthcare units. This integration enables more accurate visualization of building systems, data centralization, improved component traceability, and contributes to more assertive decision-making by maintenance managers. However, the process of consolidating and structuring information to populate the BIM model with data relevant to FM has proven to be one of the major challenges. Theoretical/Methodological Contributions – The research demonstrates the importance of a collaborative workflow using BIM model associated with FM in hospital environments, an approach that remains underexplored in the literature. Furthermore, this integration proves to be a highly useful tool with potential for further development in asset management and the centralization of operational data. Social and Environmental Contributions – The study contributes socially by improving patient quality of care and safety, optimizing resources, and creating a more functional and reliable hospital environment for healthcare professionals. Environmental contributions include reduced consumption of resources (such as energy and water), decreased use of paper for issuing work orders, and prints manuals, blueprints, and checklists, as well as improved inventory and materials management. This enhanced management helps prevent excess stock of spare parts and supplies due to the accuracy of the asset data within the model.